Relationship between body composition and cognitive abilities among young female handball players - Sliz, M.; Pasko, W.; Dziadek, B.; Ziajka, A.; Poludniak, N.; Marszalek, P.; Krawczyk, G.; Przednowek, K. (Journal of Physical Education and Sport, 2023)
The paper analyzes selected psychomotor abilities of female players practicing handball in club SPR Handball Rzeszów. Handball is a discipline characterized by fast play and high intensity. This sport requires from the player a high level of coordination and conditioning skills, which often determine the effectiveness of the athlete during the match. The speed of reaction is one of the key factors, because it makes it easier to predict the opponent's movement, pass, grip or throw the ball. The study included a group of 24 female handball players from the Polish 1st Handball League. The group was divided into two age categories (junior and senior). The research method was psychomotor computer tests in the Test2Drive system. To measure the indicators of psychomotor ability, 6 tests were used, during which the parameters of reaction time, movement time, parameters determining eye-hand coordination and anticipation were evaluated. A significant statistical difference was observed between the groups for movement time in the PUT n test. The analysis of correlations in individual groups of athletes showed that the level of selected motor skills might be affected by some parameters of body composition. In particular, it concerned the relationship between the reaction time in the SPANT test and total body water (TBW), skeletal muscle mass (SMM), body mass and height, and the CHORT test and BMI. The movement time of the subjects was affected by such parameters as higher body fat mass (FAT) and BMI (in the SIRT test), a higher basal metabolic rate index (BMR), greater skeletal muscle mass and a higher TBW (in the PUT test).